Biosorption of Metal Ions on Methanol Dehydrogenase Enzymatic Activity of Bradyrhizobium japonicum USDA110 - Novita Kurniawati; Ambar Pertiwiningrum; Yuny Erwanto; Nanung Agus Fitriyanto; Mohammad Zainal Abidin (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
This research aims to understand the effect of metal ions bioabsorption which belong on different elemental groups to the methanol dehydrogenase (MDH) enzymatic activity in nitrogen-fixing bacteria Bradyhizobium japonicum USDA 110. Ten metal ions with each have 30μM concentration were added to grow Bradyhizobium japonicum USDA 110 in 10-1 diluted nutrient medium. The MDH activity test showed a similar result between the bacteria grown in medium without metal ions addition (control) and the bacteria were grown in a calcium ion/Ca2+ added media. The highest MDH enzymatic activity was shown on the bacteria grown in a magnesium/Mg2+ added medium, which showed 0.08 (U/mg) enzymatic activities. The addition of magnesium/Mg2+ metal ion accelerates the bacterial growth by 2.6 times and MDH activity by 1.28 times compared to control. The MDH enzyme is essential, especially for bacteria which exist in the soil environment, to adapt to high methanol concentration and to support bacterial anaerobic growth capacity along with plant symbiotic process. Moreover, the MDH activity staining method could also act as pollutant indicators like metal ions and hydrocarbon derivates. This research concluded that metal ions biosorption (calcium/Ca2+ and magnesium/Mg2+) are required for bacterial cells reproduction and oxidation of single carbon chain compounds like methanol. The nitrogen-fixing symbiotic bacteria, Bradyhizobium japonicum USDA 110 showed high MDH activity after the two metal ions absorption. However, contrary results were shown on vanadium/V3+, manganese/Mn2+, iron/Fe3+, copper/Cu2+, zinc/Zn2+, and aluminum/Al3+ absorption, which showed low MDH activity and cells biomass.